Polish Teachers’ Salaries in 1990-2015 - Antoni Józef JEŻOWSKI (Expert Journal of Economics, 2015)
The earnings of the largest professional group financed with public resources, which participates in the realization and financing of the most common and the most expensive public service is the cause of industrial disputes on one hand, and pay aspirations on the other. At the same time the analysis of this phenomenon from the perspective of the public budget as the payer and the scientist-researcher as an analyst often leads to surprising conclusions concerning both the allocation of public means in time and social justice.